Transformation of Pinb-D1x to soft wheat produces hard wheat kernel texture. (January 2020) - Ma, Xiaoling; Xue, Hui; Sun, Jiazhu; Sajjad, Muhammad; Wang, Jing; Yang, Wenlong; Li, Xin; Zhang, Aimin; Liu, Dongcheng
Abstract: Kernel hardness - a key quality trait of common wheat ( Triticum aestivum L.) - is mainly conditioned by the Pina and Pinb genes. Mutation or deletion of Pina or Pinb increases kernel hardness, resulting in a hard wheat kernel texture. Here, Pinb-D1x gene was cloned from a hard wheat landrace Kashibaipi and transformed into a soft wheat cultivar Yangmai19 to assess its effect on kernel hardness and flour properties. PCR, RT-PCR and Western blot data confirmed the successful transformation and overexpression of Pinb-D1x gene in transgenic offsprings. The data of single kernel characterization system and scanning electron microscopy revealed that the introduction of Pinb-D1x in soft wheat increased the kernel hardness significantly and changed the internal structure of the kernel. Similarly, transgenic lines exhibited hard wheat like flour properties; flour whiteness and pasting temperature were significantly reduced in the transgenic lines, while the total protein content, damaged starch content, and compound parameter in the Mixograph tests (PT × TW value) showed a significant increase over the wildtype. The results showed that the transformation of the Pinb variants is a powerful strategy to alter the kernel hardness and flour properties in wheat breeding. Graphical abstract: Scanning election micrographs of endosperm structures of the wildtype Yangmai19 and Pinb-D1x transgenic lines. Comparing to the loose adhesion of starch granules and protein matrix in the wildtype Yangmai19 (A), the starch granules and protein matrix tightly adhered to the grain endosperm in three Pinb-D1x transgenic lines (B-D). Image 1 Highlights: The introduction of TaPinb-D1x allele into a soft wheat could significantly increase the kernel hardness. The transgenic lines were lower in PINB protein content than the wildtype wheat. The transgenic lines exhibited hard wheat flour properties.